Using Network Pharmacology to Explore the Mechanism of Panax notoginseng in the Treatment of Myocardial Fibrosis. (25th March 2022) - Han, Jingxue; Hou, Jingyi; Liu, Yu; Liu, Peng; Zhao, Tingting; Wang, Xinwei
Abstract : Objective . The mechanism of Panax notoginseng in treating myocardial fibrosis (MF) was investigated using network pharmacology. Methods . Effective ingredients and potential targets of Panax notoginseng were screened in relevant databases to construct a compound-target network. Targets of MF were then screened to select common targets and construct a protein-protein interaction network. This was followed by Gene Ontology and pathway enrichment analyses. Molecular docking then verified the results of network analysis. Results . A total of 14 effective ingredients and 119 potential targets for MF were predicted. Quercetin, beta-sitosterol, and gossypetin were speculated to be the main active ingredients. The mechanism of action may be related to AGE-RAGE, proteoglycans, and IL-17 signaling pathways. Five key targets (IL6, ALB, AKT1, TNF, and VEGFA) may be involved in the treatment of MF using Panax notoginseng. Conclusions . This study embodies the complex network relationship of multicomponents, multitargets, and multipathways of Panax notoginseng in treating MF and provides a novel method for further research on this herb's mechanism.